Molecular Characteristics Study of The Plants of Two Species Form The Genus Eruca Mill of The Brassicaceae Family, Which are Growing in Iraq - Ghassan Radam Idan Al.Taie (Nabatia, 2023)
The Internal Transcribed Spacer ITS method was used to diagnose the two species (Eruca sativa Mill. And Eruca vesicaria L.) These plants belong to the Eruca Mill genus from the Brassicaceae family. This study was conducted during the spring season of the year (2022-2023), as all samples were taken from different regions in Iraq, after being classified from the Iraqi flora. (E. sativa Mill and E. vesicaria L) of the Brassicaceae family to find out the degree of relatedness between the two species. of wildly growing plants in iraq, as the Deoxyribonucleic acid DNA bundles were extracted from agarose gel and the process of finding the sequence of nitrogenous bases was performed. Eruca two species. E. sativa Mill. And E. vesicaria L. which belong to the Brassicaceae family. With a percentage of 100% and 99.83% concordance. This method is considered one of the accurate methods in the diagnosis of genus at the level of the one species and between two species in addition to its ease to compare and and differentiate between the two species.